Analisis Penyebab Utama Cacat Produk Flashing pada Proses Plastik Injeksi di PT ATMI IGI CENTER - Sapto Bagus Pamungkas (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2025)
ATMI IGI CENTER (AIC) is companies in Surakarta city engaged iin the field of plastic injection. This company provides various plastic products such as household products, agriculture, automotive, hospitals and electronics. AIC in the production process is often faced with defective products that directly affect productivity both in terms of wasting time or materials because they must repeat the process, but also affect customer assessments due to late delivery, one of the product defects that often occurs is flashing defects. This study aims to analyze the main causes of flashing defects in the plastic injection process, focusing on the influence of process parameters, Mold conditions, and materials used. The research method involves collecting production data, visual inspection of defective products, and analyzing machine and Mold conditions. The results of the study showed that flashing defects were caused by several main factors, namely excessive injection pressure and wear on the Mold surface. Improvement efforts were made by optimizing process parameters, routine Mold maintenance. With the implementation of these improvements, the level of defective products was significantly reduced. This study is expected to be a reference for the plastic injection industry to minimize flashing defects and increase production efficiency.